Calculation of temperature distribution and rheological properties of the lithosphere along geotransect in the Red Sea region - DÉREROVÁ, Jana; KOHÚT, Igor; RADWAN, Anwar H.; BIELIK, Miroslav (Contributions to Geophysics and Geodesy, 2017)
The temperature model of the lithosphere along profile passing through the Red Sea region has been derived using 2D integrated geophysical modelling method. Using the extrapolation of failure criteria, lithology and calculated temperature distribution, we have constructed the rheological model of the lithosphere in the area. We have calculated the strength distribution in the lithosphere and constructed the strength envelopes for both compressional and extensional regimes. The obtained results indicate that the strength steadily decreases from the Western desert through the Eastern desert towards the Red Sea where it reaches its minimum for both compressional and extensional regime. Maximum strength can be observed in the Western desert where the largest strength reaches values of about 250–300 MPa within the upper crust on the boundary between upper and lower crust. In the Eastern desert we observe slightly decreased strength with max values about 200–250 MPa within upper crust within 15 km with compression being dominant. These results suggest mostly rigid deformation in the region or Western and Eastern desert. In the Red Sea, the strength rapidly decreases to its minimum suggesting ductile processes as a result of higher temperatures.